First five generations Chinese family of tuberous scleroses complex due to a new mutation of the TSC1 gene. (August 2018) - Cui, Jianfei; Yu, Xiaoman; Liang, Shuli; Zhang, Shaohui; Hu, Xiaohong
Abstract: Tuberous scleroses complex (TSC) is a rare neurocutaneous syndrome and has autosomal dominant inheritance. However, larger family with TSC is very rare. Here, we report the first five generations family with TSC from China, and localize the pathogenic gene. A boy with TSC and epilepsy underwent preoperative evaluation and epileptic surgery. His TSC family history was gotten, and the clinical data of a Chinese family with TSC were collected in 2016. Complete exons sequencing was performed in the proband and his parents, and whole exons sequence of TSC was performed in the other family members. The family showed autosomal dominant inheritance, and it was the largest reported family with TSC. In this pedigree, there were 14 patients in 5 generations, but only 1 case with epilepsy in them. All of examined patients had TSC 1 gene exon 15 c.1846delG p.A616Pfs * 13 mutation. In conclusion, TSC patients with TSC 1 deletion presented mild neurological symptom and rendered larger family.